Islamic Boarding School in Empowering Education for Women - Nurul Qolbi Kurniawati (International Journal Labs, 2022)
Pesantren as an educational institution in historical disabilities provides a great contribution to the progress of the nation and state through struggles in the field of education. On the other hand, Pesantren are often identified with conservatism because they are resistant to values that come from outside, including the values of gender equality. However, it cannot be only seen from the stigma of Pesantren which is synonymous with gender inequality. Pesantren also participates in empowerment efforts and women through education. With education women are able to become independent individuals, empowered and able to have a role in society. Data collection in this study through observation, interviews and supported some literature. The results of this study show that Pesantren is able to provide empowerment in the field of women's education.